Riquiqui and Minibrain, new regulators of the Hippo pathway downstream of Dachsous - Degoutin, Joffrey (2013)
The atypical cadherins, Fat (Ft) and Dachsous (Ds) control tissue growth via the Salvador-Warts-Hippo (SWH) pathway, and also regulate planar cell polarity (PCP), proximo-distal (PD) patterning and morphogenesis. Ft and Ds engage in reciprocal signalling as both proteins can serve as receptor and ligand for each other. The intracellular domains (ICD) of Ft and Ds regulate activity of the key SWH pathway transcriptional co-activator protein Yorkie (Yki). Signalling from the Ft ICD is well characterized and controls tissue growth by regulating abundance of the Ykirepressive kinase Warts (Wts). Here we describe two new regulators of the SWH pathway that function downstream of the Ds ICD: the WD40 domain protein Riquiqui (Riq) and the DYRK-family kinase Minibrain (Mnb). Ds physically interacts with Riq, which forms a complex with both Mnb and Wts. Riq and Mnb promote Ykidependent tissue growth by stimulating phosphorylation-dependent inhibition of Wts. Thus, we describe a new branch of the SWH pathway that promotes tissue growth downstream of Ds.